Composite diaphragm for aqueous zinc-based battery as well as preparation method and application of composite diaphragm

By using a low melting point network binder to combine the anti-dendrite separator and the hydrophilic separator, the problems of zinc metal dendrite growth and cathode active material dissolution in aqueous zinc-ion batteries are solved, achieving long-term cycle stability and stability of the battery. High energy storage performance.

CN119361969AActive Publication Date: 2025-01-24TOWNGAS CHINA ENERGY TECH (SHENZHEN) CO LTD +1

Patent Information

Application Number
CN202411929943.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

During the charging and discharging process of existing aqueous zinc ion batteries, zinc metal grows in dendrite and pierces the separator due to uneven deposition of the negative electrode interface, causing a short circuit, limiting the cycle life of the battery; at the same time, the positive electrode material has severe active substance dissolution, Capacity attenuation problem reduces the battery's long-term energy storage performance.

Method used

By using a low melting point mesh adhesion, a double or multi -layer anti -branched crystal diaphragm and hydrophilic diaphragm are simply compounded to avoid the difficulty of local modification when different functions on both sides of a single diaphragm. The pulp immersion and soaking method are used in situ, etc.

Benefits of technology

Realize separate preparation and composite of each layer with different functions, reduce production complexity, improve applicability, effectively solve the problem of dissolving negative branches and positive active substances of zinc ion batteries, and improve the cycle of batteries. Stability and energy storage performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361969A_ABST
    Figure CN119361969A_ABST
Patent Text Reader

Abstract

The invention provides a composite diaphragm for an aqueous zinc-based battery and a preparation method and application thereof, and the preparation method comprises the following steps: carrying out the following hydrophilization treatment on a diaphragm base material to obtain a hydrophilic diaphragm: placing the diaphragm base material in a grafting reactor, adding an acidizing solution with the volume concentration of 1-70%, and enabling the acidizing solution to completely immerse the diaphragm base material to obtain a hydrophilic diaphragm; the ratio of the volume of the acidizing solution to the area of the diaphragm base material is 0.01-1; the grafting reactor is sealed and heated to 30-90 DEG C for a grafting reaction, and the heating time is 2-72 h; and putting the diaphragm base material subjected to the grafting reaction into deionized water, soaking and washing for 5-120 minutes, and drying, so as to obtain the hydrophilic diaphragm subjected to grafting modification, and sequentially stacking the anti-dendritic diaphragm, the reticular binder and the hydrophilic diaphragm, and compounding to obtain the composite diaphragm. The composite diaphragm can effectively prevent the generation of battery negative electrode dendritic crystals and improve the stability of a battery positive electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery separators, and in particular to a composite separator for aqueous zinc-based batteries and a preparation method and application thereof. Background Art

[0002] Among the existing electrochemical energy storage systems, zinc metal, as a metal with stable chemical properties and abundant reserves, has low production and battery assembly costs, so aqueous zinc-ion batteries have the basic conditions for large-scale energy storage. However, during the charge and discharge process of aqueous zinc-ion batteries, due to the uneven deposition of the negative electrode interface, the zinc metal grows in a dendritic shape and punctures the diaphragm to cause a short circuit, thereby limiting the cycle life of the battery; at the same time, on the positive electrode side, the currently commonly used halogen, manganese-based, and vanadium-based materials have serious problems of active material dissolution and capacity attenuation, which reduces the long-term energy storage performance of the battery. The problems existing in the positive and negative electrodes of zinc-ion batteries can be solved by using battery separators and modifying the battery separators.

[0003] Existing dual-interface membranes usually choose to introduce functional layers on both sides of a monolithic membrane to achieve simultaneous optimization of the positive and negative electrodes. In order to achieve a dual interface, it is usually necessary to adopt methods such as vapor deposition, immersion depth control, and pre-covering to prevent the modification on one side from diffusing to the other side. This limits the choice of membrane matrix materials to a certain extent and also leads to higher production complexity. Some simple solution immersion modification methods are difficult to apply to similar dual-interface membrane systems. Summary of the invention

[0004] The present application provides a composite diaphragm for an aqueous zinc-based battery, and a preparation method and application thereof. By using a low-melting-point mesh adhesive, a double-layer or multi-layer anti-dendrite diaphragm and a hydrophilic diaphragm are simply composited, which can avoid the difficulty of local modification when constructing different functions on both sides of a single diaphragm. Each layer of diaphragm with different functions can be prepared separately and finally composited into a whole. Therefore, some simple modification methods such as slurry dipping, in-situ grafting by immersion method, etc. are allowed to be used for diaphragm modification and applied in double-interface diaphragms, which can reduce production complexity and improve applicability.

[0005] In a first aspect, an embodiment of the present application provides a composite diaphragm for an aqueous zinc-based battery, the composite diaphragm comprising: An anti-dendrite separator, wherein the first end surface of the anti-dendrite separator is bonded to the first end surface of the mesh binder, and the second end surface of the anti-dendrite separator is the end surface of the composite separator close to the negative electrode side of the aqueous zinc-based battery; A hydrophilic separator, wherein the first end face of the hydrophilic separator is bonded to the second end face of the mesh binder, and the second end face of the hydrophilic separator is the end face of the composite separator close to the positive electrode side of the aqueous zinc-based battery.

[0006] In a possible implementation manner, the hydrophilic membranes are multiple layers, and any two adjacent layers of the hydrophilic membranes are bonded together by a single layer of mesh adhesive.

[0007] In a possible implementation, the anti-dendrite membrane has multiple layers, and any two adjacent anti-dendrite membranes are bonded together by the single-layer mesh adhesive, and the composite membrane includes at least one anti-dendrite membrane and one hydrophilic membrane.

[0008] In a possible embodiment, the membrane substrates of the hydrophilic membrane and the anti-dendrite membrane are respectively one of polyester fiber membranes, cellulose fiber membranes, polyolefin fiber membranes, polyamide fiber membranes and glass fiber membranes, or a mixed membrane composed of multiple fiber membranes, and the membrane substrate is subjected to a hydrophilic treatment to obtain the hydrophilic membrane, and the hydrophilic treatment includes a grafting treatment; The web binder is a fiber web composed of an organic polymer, wherein the components of the organic polymer include one or more of polyvinylidene fluoride, polytetrafluoroethylene, hydroxymethyl cellulose and cellulose acetate.

[0009] In one possible embodiment, the surface of the anti-dendrite separator includes a plurality of active groups capable of inducing zinc ion deposition behavior; The surface of the hydrophilic membrane includes a plurality of hydrophilic groups and a plurality of active groups, and the plurality of hydrophilic groups and the plurality of active groups are used to improve the hydrophilicity of the hydrophilic membrane; The surface of the fiber web of the web-like adhesive comprises a plurality of polar groups, and the plurality of polar groups are used to enhance the adhesiveness of the web-like adhesive.

[0010] In a possible implementation, the surface of the anti-dendrite membrane includes a plurality of pores arranged in an orderly array, and the pore size specification of the anti-dendrite membrane is 50-1000 mesh.

[0011] In a possible embodiment, the surface density of the web-shaped binder is 0.5-50 mg / .

[0012] In a second aspect, the present application embodiment provides a method for preparing a composite diaphragm for an aqueous zinc-based battery, which is applied to the composite diaphragm for an aqueous zinc-based battery as described in the first aspect of the present application embodiment, and the method comprises: The membrane substrate is subjected to the following hydrophilization treatment to obtain a hydrophilic membrane: The membrane substrate is placed in a grafting reactor, and an acidified solution with a volume concentration of 1%-70% is added to completely immerse the membrane substrate. The ratio of the volume of the acidified solution to the area of ​​the membrane substrate is 0.01-1 ml / ;as well as, The grafting reactor is sealed and heated to 30-90° C. to carry out the grafting reaction, and the heating time is 2-72 h; and, After the grafting reaction is completed, the membrane substrate is soaked and washed in deionized water for 5-120 minutes, and then dried to obtain the hydrophilic membrane after grafting modification; The anti-dendrite membrane, the mesh adhesive and the hydrophilic membrane are stacked in sequence and compounded to obtain the composite membrane.

[0013] In a possible implementation, the lamination method includes hot rolling lamination, flat plate hot pressing lamination and room temperature pressure bonding, and the temperature of the hot rolling lamination is 30-100°C.

[0014] In a third aspect, an embodiment of the present application provides an aqueous zinc-based battery, comprising a positive electrode, a negative electrode, an electrolyte and a composite diaphragm, wherein the negative electrode is a zinc-based material, the electrolyte comprises a 0.5-3 mol / L aqueous zinc sulfate solution and / or an aqueous zinc trifluoromethanesulfonate solution, and the composite diaphragm is the composite diaphragm for an aqueous zinc-based battery as described in the first aspect of the embodiment of the present application.

[0015] It can be seen that in the embodiment of the present application, a hydrophilic membrane is obtained by hydrophilizing the membrane substrate, and an anti-dendrite membrane of a specific size, substrate and structure is selected to be composited, thereby obtaining multiple hydrophilic membranes and multiple anti-dendrite membranes, and bonding two adjacent membranes by selecting a mesh binder with a specific substrate and surface density, thereby bonding multiple hydrophilic membranes and multiple anti-dendrite membranes, and further composite, an anti-dendrite-hydrophilic double interface composite membrane can be obtained. In this way, relative to the existing scheme of modifying both sides of a monolithic membrane to form a double interface membrane, the present application forms a double interface composite membrane by preparing and simply modifying multiple monolithic membranes respectively, which can be applied to a variety of modified materials and membrane substrates of different compositions, effectively solving the dendrite problem of the zinc negative electrode of the aqueous zinc ion battery and the large demand for positive electrolyte. At the same time, the preparation process of the double interface composite membrane is relatively simple, which can reduce the complexity of production and improve applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1Schematic diagram of a composite diaphragm for an aqueous zinc-based battery provided in an embodiment of the present application; Figure 2 It is a flow chart of a method for preparing a composite diaphragm for an aqueous zinc-based battery provided in an embodiment of the present application; Figure 3 This is a Fourier transform infrared spectrum comparison diagram of a cellulose membrane before and after hydrophilic treatment provided in an embodiment of the present application; Figure 4 is a voltage-time curve diagram of a battery including a dual-interface composite diaphragm provided in an embodiment of the present application; Figure 5 This is a hydrogen evolution and oxygen evolution curve of a battery including a double-interface composite membrane provided in an embodiment of the present application. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0019] The terms "first", "second", etc. in the specification and claims of this application and the above-mentioned drawings are used to distinguish different objects, rather than to describe a specific order. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not limited to the listed steps or units, but optionally includes steps or units that are not listed, or optionally includes other steps or units inherent to these processes, methods, products or devices.

[0020] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0021] In the embodiments of the present application, "and / or" describes the association relationship of the associated objects, indicating that three relationships may exist. For example, A and / or B can represent the following three situations: A exists alone; A and B exist at the same time; B exists alone. Among them, A and B can be singular or plural.

[0022] In the embodiment of the present application, the symbol " / " can indicate that the objects associated with each other are in an "or" relationship. In addition, the symbol " / " can also indicate a division sign, that is, performing a division operation. For example, A / B can indicate A divided by B.

[0023] In the embodiments of the present application, "equal to" can be used in conjunction with greater than, and is applicable to the technical solution adopted when greater than, and can also be used in conjunction with less than, and is applicable to the technical solution adopted when less than. When equal to is used in conjunction with greater than, it is not used in conjunction with less than; when equal to is used in conjunction with less than, it is not used in conjunction with greater than.

[0024] Currently, existing dual-interface membranes usually choose to introduce functional layers on both sides of a monolithic membrane to achieve simultaneous optimization of the positive and negative electrodes. In order to achieve a dual interface, it is usually necessary to adopt methods such as vapor deposition, immersion depth control, and pre-covering to prevent the modification on one side from diffusing to the other side. This limits the choice of membrane matrix materials to a certain extent and also leads to higher production complexity. Some simple solution immersion modification methods are difficult to apply to similar dual-interface membrane systems. In view of the above problems, the embodiments of the present application provide a composite diaphragm for an aqueous zinc-based battery and a preparation method and application thereof. The embodiments of the present application are described in detail below in conjunction with the accompanying drawings.

[0025] See also Figure 1 , Figure 1 Schematic diagram of a composite diaphragm for an aqueous zinc-based battery provided in an embodiment of the present application, wherein the composite diaphragm for an aqueous zinc-based battery comprises an anti-dendrite diaphragm and a hydrophilic diaphragm.

[0026] The composite membrane includes an anti-dendrite membrane and a plurality of hydrophilic membranes, and any adjacent membranes are bonded with a mesh adhesive, and the bonded multi-layer membranes need to be compounded to form a composite membrane. The compounding method includes but is not limited to hot-melt compounding of each membrane layer by hot rolling, and compounding of the membrane by flat plate hot pressing and normal temperature pressure bonding.

[0027] In one possible embodiment, a composite separator for an aqueous zinc-based battery comprises: An anti-dendrite separator, wherein the first end surface of the anti-dendrite separator is bonded to the first end surface of the mesh binder, and the second end surface of the anti-dendrite separator is the end surface of the composite separator close to the negative electrode side of the aqueous zinc-based battery; A hydrophilic separator, wherein the first end face of the hydrophilic separator is bonded to the second end face of the mesh binder, and the second end face of the hydrophilic separator is the end face of the composite separator close to the positive electrode side of the aqueous zinc-based battery.

[0028] In a possible embodiment, the hydrophilic membranes are multiple layers, and any two adjacent layers of the hydrophilic membranes are bonded together by a single layer of mesh adhesive.

[0029] In a possible embodiment, the anti-dendrite membrane has multiple layers, and any two adjacent anti-dendrite membranes are bonded together by the single-layer mesh adhesive, and the composite membrane includes at least one anti-dendrite membrane and one hydrophilic membrane.

[0030] It is understandable that the composite diaphragm is at least a two-layer diaphragm, and in specific circumstances, three or more layers of diaphragms are required. The use of multi-layer diaphragms mainly includes applications in high-energy density batteries. For high-energy density batteries, in order to improve safety, a three-layer or more diaphragm structure will be adopted, which can improve the mechanical strength and thermal stability of the diaphragm and reduce the risk of short circuit; and includes applications in high-power batteries. For high-power batteries, such as power batteries, multi-layer diaphragms can improve ion transmission capabilities, reduce internal resistance, and thus increase power output; and includes applications in special environments, such as high temperature and high humidity environments, where multi-layer diaphragms can provide better isolation performance and durability; and includes applications in special material batteries, such as solid-state batteries, where multi-layer diaphragms can improve interface stability and reduce interface resistance.

[0031] In a possible embodiment, the membrane substrates of the hydrophilic membrane and the anti-dendrite membrane are respectively one of polyester fiber membrane, cellulose fiber membrane, polyolefin fiber membrane, polyamide fiber membrane and glass fiber membrane, or a mixed membrane composed of multiple fiber membranes, and the membrane substrate is subjected to a hydrophilic treatment to obtain the hydrophilic membrane, and the hydrophilic treatment includes a grafting treatment; The web binder is a fiber web composed of an organic polymer, wherein the components of the organic polymer include one or more of polyvinylidene fluoride, polytetrafluoroethylene, hydroxymethyl cellulose and cellulose acetate.

[0032] Among them, grafting is a common method of hydrophilization. Grafting involves chemically reacting another organic molecule (called a grafting agent) with the original matrix (such as a polymer or fiber). This treatment can significantly change the surface properties of the matrix, making it more hydrophilic. The specific steps of grafting usually include the following aspects: (1) Selecting an appropriate grafting agent: Select a suitable grafting agent according to the needs. These grafting agents are usually hydrophilic, such as amino acids, sugars or other molecules containing multiple functional groups; (2) Activating the matrix: Activating the matrix (such as a polymer or fiber) so that it can react chemically with the grafting agent. Common methods include using covalent bonds, ionic bonds or free radicals; (3) Grafting reaction: The grafting agent reacts with the activated matrix to attach new molecular chains or functional groups to the surface of the matrix; (4) Post-treatment: Some post-treatment steps, such as washing and dehydration, may be required to remove excess grafting agents and other impurities. Grafting can improve hydrophilicity, that is, increase the surface activity of the membrane, making it easier to interact with water molecules or other hydrophilic substances.

[0033] In a possible embodiment, the surface of the anti-dendrite membrane includes a plurality of active groups capable of inducing zinc ion deposition behavior; The surface of the hydrophilic membrane includes a plurality of hydrophilic groups and a plurality of active groups, and the plurality of hydrophilic groups and the plurality of active groups are used to improve the hydrophilicity of the hydrophilic membrane; The surface of the fiber web of the web-like adhesive comprises a plurality of polar groups, and the plurality of polar groups are used to enhance the adhesiveness of the web-like adhesive.

[0034] Specifically, the anti-dendrite membrane is a fiber membrane whose surface contains active groups and spatial structures that have an inducing effect on the deposition behavior of zinc ions; the hydrophilic membrane is a fiber membrane composed of fiber membrane materials rich in hydrophilic and polar groups and other fiber membrane materials modified or coated with hydrophilic and polar groups; the mesh binder is a fiber mesh membrane with an organic polymer rich in polar groups as the main component.

[0035] It can be understood that the composite diaphragm in the embodiment of the present application is mainly used in zinc-ion batteries. When the diaphragm substrate and components of the anti-dendrite diaphragm, hydrophilic diaphragm and mesh binder are changed, it can be applied to other batteries, such as lithium batteries, sodium batteries, calcium batteries, potassium batteries, aluminum batteries and other battery fields. Furthermore, the selected diaphragm substrate and mesh binder composition need to be adapted to the type of battery used.

[0036] For example, when applied to zinc batteries, polyester films, polyolefin films, and cellulose films with good chemical stability and mechanical strength can be selected, and polyvinylidene fluoride (PVDF) with excellent electrochemical stability and bonding properties can be selected as the component of the network binder; when applied to lithium batteries, polyolefin films (such as polyethylene PE and polypropylene PP) can be selected, which have good ionic conductivity and thermal stability, and polyvinylidene fluoride (PVDF) can be selected as the component of the network binder; when applied to sodium batteries, polyester films and polyolefin films can be selected, and polyvinylidene fluoride (PVDF) or hydroxymethyl cellulose (HPMC) can be selected as the network binder. The diaphragm substrate and network binder components used in other different types of batteries need to be specifically determined in combination with the battery characteristics and usage conditions. Only some examples of some battery types are given here.

[0037] In a possible embodiment, the surface of the anti-dendrite membrane includes a plurality of pores arranged in an orderly array, and the pore size specification of the anti-dendrite membrane is 50-1000 mesh.

[0038] It can be understood that the anti-dendrite membrane selects a densely woven fiber membrane with an ordered structure. The ordered array pores of its densely woven structure can induce the deposition array of zinc metal through physical confinement, and inhibit the formation of dendrites through dispersed deposition sites, thereby reducing the risk of dendrites piercing the membrane and short-circuiting.

[0039] In a possible embodiment, the surface density of the mesh binder is 0.5-50 mg / .

[0040] It can be seen that in this embodiment, the composite membrane includes multiple anti-dendrite membranes and multiple hydrophilic membranes. The adjacent membranes are bonded by a mesh adhesive and then compounded to obtain the composite membrane. The composite membrane is not limited to being used as a battery membrane alone, but can also be used as a functional layer stacked and combined with other membranes in a battery, wherein the hydrophilic membrane faces the positive electrode side of the aqueous zinc-based battery, and the anti-dendrite membrane faces the negative electrode side of the aqueous zinc-based battery, so that the battery can maintain good electrolyte storage capacity and anti-dendrite performance, which helps to improve the energy density of the whole battery and promote the long cycle stability of the battery.

[0041] See also Figure 2 , Figure 2 is a flow chart of a method for preparing a composite membrane for an aqueous zinc-based battery provided in an embodiment of the present application, wherein a nylon filter membrane is selected as an anti-dendrite membrane, and a cellulose membrane is selected for hydrophilization treatment to form a hydrophilic membrane, such as Figure 2As shown, the preparation method of the composite diaphragm for aqueous zinc-based batteries comprises the following steps: (1) soaking and heating a cellulose membrane in a phytic acid solution to obtain an acidified cellulose membrane; wherein the acidified cellulose membrane can be used as a hydrophilic diaphragm. (2) stacking the acidified cellulose membrane, a mesh binder and a nylon filter membrane, and then hot rolling them to obtain a composite double-interface diaphragm. (3) assembling the composite double-interface diaphragm into an aqueous zinc-ion battery.

[0042] In a possible embodiment, the method for preparing the composite diaphragm for an aqueous zinc-based battery comprises: The membrane substrate is subjected to the following hydrophilization treatment to obtain a hydrophilic membrane: The membrane substrate is placed in a grafting reactor, and an acidified solution with a volume concentration of 1%-70% is added to completely immerse the membrane substrate. The ratio of the volume of the acidified solution to the area of ​​the membrane substrate is 0.01-1 ml / ;as well as, The grafting reactor is sealed and heated to 30-90° C. to carry out the grafting reaction, and the heating time is 2-72 h; and, After the grafting reaction is completed, the membrane substrate is soaked and washed in deionized water for 5-120 minutes, and then dried to obtain the hydrophilic membrane after grafting modification; The anti-dendrite membrane, the mesh adhesive and the hydrophilic membrane are stacked in sequence and compounded to obtain the composite membrane.

[0043] In a possible embodiment, the lamination method includes hot rolling lamination, flat plate hot pressing lamination and room temperature pressure bonding, and the temperature of the hot rolling lamination is 30-100°C.

[0044] Among them, the diaphragm substrate used on the positive electrode side of the battery is hydrophilic after treatment. The hydrophilic treatment includes grafting reaction. Grafting reaction refers to the reaction of grafting a monomer or polymer chain onto another polymer chain. By introducing specific functional groups (such as hydroxyl, amino, amide, ester) into the molecular chain of the positive electrode side substrate film, its surface properties are changed, making it more suitable for use as a hydrophilic diaphragm on the positive electrode side. During the grafting reaction, the role of the acidified solution is to provide the acidic environment required for the reaction and promote the occurrence of the grafting reaction.

[0045] Wherein, the acidifying solution is an inorganic acid such as nitric acid, sulfuric acid, phosphoric acid, or an organic acid solution containing carboxyl, phosphoric acid, or sulfonic acid. Further, different acidifying solutions can be selected to be suitable for different battery environments. For example, organic carboxylic acid and organic sulfonic acid solutions can be used for modifying the lyophilic diaphragm on the positive electrode side of lithium ion batteries, nitric acid solutions and organic phosphoric acid solutions can be used for modifying the hydrophilic diaphragm on the positive electrode side of sodium ion batteries, sulfuric acid solutions and phosphoric acid solutions can be used for modifying the hydrophilic diaphragm on the positive electrode side of calcium ion batteries, and nitric acid solutions and organic phosphoric acid solutions can be used for modifying the hydrophilic diaphragm on the positive electrode side of potassium ion batteries. The embodiments of this application only provide acidifying solutions that are more suitable for grafting reactions of several different types of batteries, and are not limited to using the acidifying solutions for grafting reactions.

[0046] In a possible embodiment, the hydrophilic membranes are multiple layers, and any two adjacent layers of the hydrophilic membranes are bonded together by a single layer of mesh adhesive.

[0047] In a possible embodiment, the anti-dendrite membrane has multiple layers, and any two adjacent anti-dendrite membranes are bonded together by the single-layer mesh adhesive, and the composite membrane includes at least one anti-dendrite membrane and one hydrophilic membrane.

[0048] In a possible embodiment, the membrane substrates of the hydrophilic membrane and the anti-dendrite membrane are respectively one of polyester fiber membrane, cellulose fiber membrane, polyolefin fiber membrane, polyamide fiber membrane and glass fiber membrane, or a mixed membrane composed of multiple fiber membranes, and the membrane substrate is subjected to a hydrophilic treatment to obtain the hydrophilic membrane, and the hydrophilic treatment includes a grafting treatment; The web binder is a fiber web composed of an organic polymer, wherein the components of the organic polymer include one or more of polyvinylidene fluoride, polytetrafluoroethylene, hydroxymethyl cellulose and cellulose acetate.

[0049] In a possible embodiment, the surface of the anti-dendrite membrane includes a plurality of active groups capable of inducing zinc ion deposition behavior; The surface of the hydrophilic membrane includes a plurality of hydrophilic groups and a plurality of active groups, and the plurality of hydrophilic groups and the plurality of active groups are used to improve the hydrophilicity of the hydrophilic membrane; The surface of the fiber web of the web-like adhesive comprises a plurality of polar groups, and the plurality of polar groups are used to enhance the adhesiveness of the web-like adhesive.

[0050] In a possible embodiment, the surface of the anti-dendrite membrane includes a plurality of pores arranged in an orderly array, and the pore size specification of the anti-dendrite membrane is 50-1000 mesh.

[0051] In a possible embodiment, the surface density of the mesh binder is 0.5-50 mg / .

[0052] Furthermore, the application of the composite double interface diaphragm in aqueous zinc-based batteries, with zinc as the negative electrode, organic or inorganic materials as the positive electrode, and the composite double interface diaphragm as the battery diaphragm, 160-280 μL of electrolyte is added to assemble the battery. Specifically, the negative electrode of the aqueous zinc-based battery includes zinc sheets, zinc powder, zinc mesh, zinc foam, and composite pole pieces containing zinc metal as an active substance, etc. The positive electrode of the aqueous zinc-based battery includes an organic positive electrode and an inorganic positive electrode such as manganese dioxide, vanadium pentoxide, sodium vanadate, iodine, bromine, and the electrolyte includes 0.5-3 mol / L of zinc sulfate and / or zinc trifluoromethanesulfonate.

[0053] The anti-dendritic layer of the composite double-interface separator is oriented toward the zinc negative electrode side, and the hydrophilic layer is oriented toward the positive electrode side.

[0054] It can be seen that in this embodiment, the diaphragm substrate on the positive electrode side of the aqueous zinc-based battery is acidified and hydrophilically modified by an in-situ grafting method by immersion, so that the acidic component is bonded to the substrate membrane, and the in-situ modification of the phosphate group is achieved to form a hydrophilic diaphragm. Compared with the existing coating process and vapor deposition methods, the preparation equipment requirements are low, the production efficiency is high, the scale can be expanded, and the production efficiency of the diaphragm modification is improved; and, a densely woven fiber membrane with an ordered structure is applied to the negative electrode side of the aqueous zinc-based battery. The ordered array pores of its densely woven structure can induce the deposition array of zinc metal through physical confinement, and the formation of dendrites is suppressed through dispersed deposition sites, thereby reducing the risk of dendrites piercing the diaphragm and short-circuiting.

[0055] See also Figure 3 , Figure 3 is a Fourier transform infrared spectrum comparison diagram of a cellulose membrane before and after hydrophilic treatment provided in an embodiment of the present application, wherein the cellulose membrane is used to prepare a hydrophilic diaphragm, and the acidified solution used in the hydrophilic treatment is a phytic acid solution, such as Figure 3 As shown in the figure, the absorption peak of the cellulose membrane was significantly enhanced after being modified with phytic acid.

[0056] Among them, the Fourier transform infrared spectrum comparison chart includes the wavenumber-intensity curves of the cellulose membrane and the hydrophilic treated cellulose phytate membrane. The curve at the top is the wavenumber-intensity curve of the cellulose membrane, and the curve at the bottom is the wavenumber-intensity curve of the cellulose phytate membrane. and 1160.9 The absorption peak at was significantly enhanced after phytic acid modification, which was attributed to the PO and P=O bonds introduced by phytic acid. The corresponding grafting reaction sites were CO and COC bonds, indicating the effective modification of phytic acid in cellulose.

[0057] In a possible embodiment, a specific method for hydrophilizing a cellulose membrane to obtain a phytated cellulose membrane may include: measuring 12 ml of a phytic acid solution with a volume concentration of 17.5%, immersing an 8×8 cm cellulose membrane therein, sealing the container and transferring it to a 60°C oven for 24 hours to allow a grafting reaction to occur; and, taking out the cellulose membrane after the grafting reaction, soaking and washing it in deionized water for 10 minutes to remove excess unreacted raw materials, and drying the washed membrane again at 60°C for 2 hours to obtain a phytated cellulose membrane.

[0058] Furthermore, after obtaining the hydrophilic treated phytated cellulose membrane, a 300 mesh nylon filter membrane, a polyethylene-vinyl acetate fiber membrane, and a phytated cellulose membrane, all of which have a size of 8×8 cm, can be stacked in order and hot rolled at 60°C to obtain a double-interface composite membrane with nylon on one side and phytated cellulose on the other side. The nylon filter membrane is an anti-dendritic diaphragm applied to the negative electrode side of the battery, and the polyethylene-vinyl acetate fiber membrane serves as a mesh binder between adjacent diaphragms.

[0059] Furthermore, based on the three-layer composite membrane, polyethylene-vinyl acetate fiber membrane and cellulose membrane are stacked again on the side of the phytic cellulose membrane to obtain a multilayer double-interface composite membrane with a nylon filter membrane on one side and a cellulose membrane on the other side; or, polyethylene-vinyl acetate fiber membrane and nylon filter membrane are stacked again on the side of the nylon filter membrane to obtain a multilayer double-interface composite membrane with a nylon filter membrane on one side and a cellulose membrane on the other side.

[0060] It can be seen that in this embodiment, after phytic acid modification, the peak value of the phytic acid cellulose membrane is significantly enhanced, indicating the successful binding of phytic acid molecules to the cellulose membrane. The enhanced absorption peak indicates the introduction of PO and P=O bonds in the phytic acid molecules, which are essential for enhancing the hydrophilicity of the cellulose membrane. These bonds in the phytic acid molecules can not only enhance the mechanical strength of the cellulose membrane, but also enhance its hydrophilicity by forming a variety of hydrogen bonds and other interaction modes, so that the modified cellulose membrane can better interact with water molecules, thereby improving its stability and application performance in an aqueous environment.

[0061] See also Figure 4 , Figure 4 is a voltage-time curve diagram of a battery including a dual-interface composite diaphragm provided in an embodiment of the present application, wherein the battery is an assembled battery, and the assembled battery includes a zinc-zinc symmetric battery and a zinc-titanium half-cell, such as Figure 4 As shown, the voltage-time curve diagram is a voltage change curve diagram of the assembled battery after multiple charge and discharge cycles.

[0062] Among them, the positive and negative electrodes of the zinc-zinc symmetrical battery are made of zinc foil with a thickness of 100μm; the negative electrode of the zinc-titanium half-cell is made of zinc foil with a thickness of 100μm, and the positive electrode is made of titanium foil with a thickness of 30 microns; the outer functional diaphragm of the assembled battery is made of Figure 3 The negative electrode side is a nylon fiber membrane and the positive electrode side is a double-interface composite membrane modified with phytic acid; and the electrolyte is a 2 mol / L zinc trifluoromethanesulfonate aqueous solution and a 1 mol / L sodium sulfate aqueous solution, and a CR2032 button battery is assembled. The structure of the assembled battery is: positive electrode shell, zinc foil / titanium foil, electrolyte, double-interface composite membrane, electrolyte, zinc sheet, gasket, shrapnel and negative electrode shell.

[0063] Furthermore, the assembled battery was subjected to electrochemical testing, specifically including: charging and discharging the assembled button battery on a blue battery test system at room temperature. The test conditions for the zinc-zinc symmetrical battery were: the electrolyte was a 2 mol / L aqueous solution of zinc trifluoromethanesulfonate, the current density was 1 mA / , the deposition capacity is 1mAh / , and conduct a long-term charge-discharge cycle test. The test conditions used for the electrochemical test of the assembled battery in this embodiment include variables such as electrolyte density, current density, and deposition capacity, including but not limited to the values ​​involved in the embodiments of this application.

[0064] Among them, Figure 4 As shown, after the assembled battery was subjected to electrochemical testing, the symmetrical battery did not suffer from short circuit failure after 6000 hours of cycle charge and discharge under the test conditions used in the embodiment of the present application, indicating that the assembled battery is Figure 2 After the double-interface composite film is prepared by the preparation method shown, the introduction of the nylon anti-dendritic separator facing the negative electrode side of the battery in the double-interface composite film effectively promotes the uniformity of zinc deposition.

[0065] It can be seen that in this embodiment, the double-interface composite separator can effectively prevent the generation of negative electrode dendrites. When used in aqueous zinc-ion batteries, it helps to improve the energy density of the whole battery and promotes the long-cycle stability of the battery.

[0066] See also Figure 5 , Figure 5 is a hydrogen and oxygen evolution curve of a battery including a double-interface composite diaphragm provided in an embodiment of the present application, combined with Figure 4 , Figure 5 It includes a hydrogen evolution curve obtained by conducting a hydrogen evolution curve test on a zinc-zinc symmetric battery in an assembled battery and an oxygen evolution curve obtained by conducting an oxygen evolution curve test on a zinc-titanium half-cell.

[0067] Among them, the hydrogen evolution curve test is an electrochemical test method commonly used to evaluate the performance of aqueous zinc-ion batteries. Specifically, this test is mainly used to study the hydrogen release of zinc electrodes in acidic environments under different voltage conditions. By scanning the potential and observing the rate of hydrolysis reaction at different potentials, we can understand the stability of zinc electrodes at low potentials and the activity of hydrolysis reactions. By analyzing the curve, we can determine the activity of zinc electrodes at specific potentials and judge their performance in practical applications.

[0068] Among them, the oxygen evolution curve test is used to evaluate the oxygen evolution reaction behavior of the zinc-titanium half-cell at different potentials. Through the linear voltammetric test, the oxygen evolution reaction rate of the titanium electrode at different potentials can be observed to determine the stability of the electrode. Through the oxygen evolution curve test, the stability window of the titanium electrode in the electrolyte can be determined, that is, within what potential range the titanium electrode will not undergo oxygen evolution reaction. This is also very important for designing the electrochemical window of aqueous zinc-ion batteries, because the oxygen evolution reaction will lead to a decrease in battery performance and the occurrence of side reactions.

[0069] It is understood that the hydrogen evolution curve test and the oxygen evolution curve test can determine the stability of the electrode material at different potentials, thereby determining the electrochemical window of the battery and evaluating the stability of the electrode material. Through these tests, the battery design can be optimized, the occurrence of side reactions can be avoided, and the performance and cycle life of the battery can be improved.

[0070] Exemplarily, the conditions for conducting a hydrogen evolution curve test on a zinc-zinc symmetrical battery may be: using a 1 mol / L sodium sulfate aqueous solution as the electrolyte, conducting a linear voltammetric test using an electrochemical workstation, and a scan rate of 1 mV / s; and the conditions for conducting an oxygen evolution curve test on a zinc-titanium half-cell may be: using a 2 mol / L zinc trifluoromethanesulfonate aqueous solution as the electrolyte, and a scan rate of 1 mV / s.

[0071] Furthermore, the hydrogen evolution / oxygen evolution curve is as follows Figure 5 As shown, Figure 5 The hydrogen evolution curve is obtained by testing the hydrogen evolution curve of the zinc-zinc symmetric battery, and the oxygen evolution curve is obtained by testing the oxygen evolution curve of the zinc-titanium half-battery. The hydrogen evolution / oxygen evolution curve is a current-voltage curve. It can be seen that the current is 0.1mA / The use of a double-interface composite diaphragm can widen the electrochemical window of aqueous zinc-ion batteries to 2.2 V, which is the critical point of hydrogen evolution / oxygen evolution reaction. This shows that the developed diaphragm material can effectively isolate the positive and negative electrodes, prevent short circuits, and allow ions to move freely between electrodes. The introduction of acidic groups effectively inhibits the occurrence of electrode side reactions and increases the voltage selection range of electrode materials, which helps to improve the performance and stability of aqueous zinc-ion batteries.

[0072] It can be seen that in this embodiment, the anti-dendrite-hydrophilic double interface composite membrane can achieve the array-shaped zinc negative electrode morphology on the negative electrode side and the good liquid storage and ion conduction functions of the hydrophilic membrane in the application of aqueous zinc ion batteries. The zinc ion battery using the composite membrane has excellent long cycle life and stable electrochemical properties. The anti-dendrite-hydrophilic double interface composite membrane has excellent performance in aqueous zinc ion battery systems.

[0073] The above is part of the implementation methods of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A composite diaphragm for aqueous zinc-based batteries, characterized in that: include: An anti-dendrite separator, wherein the first end surface of the anti-dendrite separator is bonded to the first end surface of the mesh binder, and the second end surface of the anti-dendrite separator is the end surface of the composite separator close to the negative electrode side of the aqueous zinc-based battery; A hydrophilic separator, wherein the first end face of the hydrophilic separator is bonded to the second end face of the mesh binder, and the second end face of the hydrophilic separator is the end face of the composite separator close to the positive electrode side of the aqueous zinc-based battery.

2. The composite diaphragm for aqueous zinc-based batteries according to claim 1, characterized in that: The number of layers of the hydrophilic membrane is multiple, and any two adjacent layers of the hydrophilic membrane are bonded together by a single layer of mesh adhesive.

3. The composite diaphragm for aqueous zinc-based batteries according to claim 1 or 2, characterized in that: The anti-dendrite membrane has multiple layers, and any two adjacent anti-dendrite membranes are bonded together by the single-layer mesh adhesive. The composite membrane includes at least one anti-dendrite membrane and one hydrophilic membrane.

4. The composite diaphragm for aqueous zinc-based batteries according to claim 3, characterized in that: The membrane substrates of the hydrophilic membrane and the anti-dendrite membrane are respectively one of polyester fiber membrane, cellulose fiber membrane, polyolefin fiber membrane, polyamide fiber membrane and glass fiber membrane, or a mixed membrane composed of multiple fiber membranes, and the hydrophilic membrane is obtained by subjecting the membrane substrate to a hydrophilic treatment, wherein the hydrophilic treatment includes a grafting treatment; The web binder is a fiber web composed of an organic polymer, wherein the components of the organic polymer include one or more of polyvinylidene fluoride, polytetrafluoroethylene, hydroxymethyl cellulose and cellulose acetate.

5. The composite diaphragm for aqueous zinc-based batteries according to claim 4, characterized in that: The surface of the anti-dendrite separator includes a plurality of active groups capable of inducing zinc ion deposition behavior; The surface of the hydrophilic membrane includes a plurality of hydrophilic groups and a plurality of active groups, and the plurality of hydrophilic groups and the plurality of active groups are used to improve the hydrophilicity of the hydrophilic membrane; The surface of the fiber web of the web-like adhesive comprises a plurality of polar groups, and the plurality of polar groups are used to enhance the adhesiveness of the web-like adhesive.

6. The composite diaphragm for aqueous zinc-based batteries according to claim 5, characterized in that: The surface of the anti-dendrite membrane includes a plurality of pores arranged in an orderly array, and the pore size specification of the anti-dendrite membrane is 50-1000 mesh.

7. The composite diaphragm for aqueous zinc-based batteries according to claim 6, characterized in that: The surface density of the mesh binder is 0.5-50 mg / .

8. A method for preparing a composite diaphragm for an aqueous zinc-based battery, applied to the composite diaphragm for an aqueous zinc-based battery as claimed in claim 1, characterized in that: The method comprises: The membrane substrate is subjected to the following hydrophilization treatment to obtain a hydrophilic membrane: The membrane substrate is placed in a grafting reactor, and an acidified solution with a volume concentration of 1%-70% is added to completely immerse the membrane substrate. The ratio of the volume of the acidified solution to the area of ​​the membrane substrate is 0.01-1 ml / ;as well as, The grafting reactor is sealed and heated to 30-90° C. to carry out the grafting reaction, and the heating time is 2-72 hours; and, After the grafting reaction is completed, the membrane substrate is soaked and washed in deionized water for 5-120 minutes, and then dried to obtain the hydrophilic membrane after grafting modification; The anti-dendrite membrane, the mesh adhesive and the hydrophilic membrane are stacked in sequence and compounded to obtain the composite membrane.

9. The method according to claim 8, characterized in that The laminating method includes hot rolling laminating, flat plate hot pressing laminating and normal temperature pressure bonding, and the temperature of the hot rolling laminating is 30-100°C.

10. An aqueous zinc-based battery, characterized in that: The aqueous zinc-based battery comprises a positive electrode, a negative electrode, an electrolyte and a composite diaphragm, wherein the negative electrode is a zinc-based material, the electrolyte comprises a 0.5-3 mol / L aqueous zinc sulfate solution and / or an aqueous zinc trifluoromethanesulfonate solution, and the composite diaphragm is the composite diaphragm for an aqueous zinc-based battery according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Hydrophilic processing method for zinc nickle alkaline accumulator diaphragm

    CN101471431A

  • Inorganic / organic compound functional porous isolating membrane and preparation method as well as lithium ion battery adopting inorganic / organic compound functional porous isolating membrane

    CN105789523A

  • Multilayer composite structure separator, preparation method thereof and lithium sulfur battery

    CN109167012A

  • Composite diaphragm, preparation method and application thereof, and aqueous zinc ion battery

    CN117276809A

  • Dendritic crystal-free zinc-based battery composite electrode and preparation method and application thereof

    CN118136977A

Cited By

  • Composite diaphragm for aqueous zinc ion battery and preparation method of composite diaphragm

    CN120016083A

  • A composite separator for aqueous zinc-ion batteries and its preparation method

    CN120016083B